PENGETAHUAN LOKAL MASYARAKAT SAMIN TENTANG KEANEKARAGAMAN TUMBUHAN DAN PENGELOLAANYA - Jumari .; Dede Setiadi; Y. Purwanto; Edi Gurhardja (Media Konservasi, 2012)
The aims of the  study  is to reveal of local knowledge  the Samin society  about the diversity of plant species is usefulness, the utilization category, the potential use, value of cultural and concept of  traditional conservation. The location of observation are 7 villages: Larikrejo and Kaliyoso (Kudus);  Bombong and Ngawen (Pati); Klopoduwur and Tambak (Blora); Margomulyo (Bojonegoro).  Data collection using survey and  open ended interview techniques.  Useful plant inventory carrying more than 235 species of plants; as 118 species of food; ingredient in traditional medicines 74 species: 16 species of building materials; equipment and craft materials 15 species: 16 species of firewood; 27 species of animal feed; fiber materials and rope three species, two species of fish poisons; pest control materials 16 species and  ornamental plants 25 species. The most of  useful plant species (80% ) are cultivated plant and  25% intensity value  utilization of this species is high. The results of calculation of the Indeks of Cultural Signification found the species that have important value is the highest Oryza sativa L. and  the second  is Tectona grandis L.f.  Keyword: local knowledge, plant diversity, plant conservation, Indeks of Cultural Signification, Samin Society